THU0635 Defining The Optimal Biological Monotherapy in Rheumatoid Arthritis: A Systematic Review and Network Meta-Analysis of Randomised Trials. (15th July 2016) - Tarp, S.; Furst, D.E.; Døssing, A.; Østergaard, M.; Lorenzen, T.; Hansen, M.; Singh, J.; Choy, E.; Boers, M.; Suarez-Almazor, M.; Kristensen, L.; Bliddal, H.; et al.
Abstract : Background: Many rheumatoid arthritis (RA) patients might not tolerate or adhere to conventional synthetic DMARDs, it is therefore important to evaluate use of biological agents as monotherapy. Objectives: To summarise and compare the benefits and harms of biological agents used as monotherapy for RA. Methods: We searched MEDLINE, EMBASE, the Cochrane Central Register of Controlled Trials and other sources for randomised trials that compared biological monotherapy with MTX, placebo, or other biological monotherapies. Primary outcomes were ACR50 and the number of patients who discontinued due to adverse events. Our network meta-analysis was based on mixed-effects logistic regression, including both direct and indirect comparisons of the treatment effects, whilst preserving the randomised comparisons within each trial. Results: The analysis comprises 28 trials (8, 602 patients), including all nine biological agents approved for RA. Of the included trials, 8 (29%) included "DMARD-naïve", and 20 (71%) "DMARD-Inadequate responder" (DMARD-IR) patients. All agents except anakinra and infliximab were superior to placebo with regard to ACR50 (Figure ). Etanercept and rituximab were superior to anakinra. Tocilizumab was superior to adalimumab, anakinra, certolizumab, and golimumab. When including only DMARD-IR trials, the same statistical pattern emerged, complemented with superiority of etanercept and tocilizumab compared with abatacept. Focusing on recommended doses, both etanercept and tocilizumab were superior to adalimumab and certolizumab. No differences in benefit among etanercept, tocilizumab, and rituximab were found. However, because rituximab was evaluated in just 40 patients, our confidence in the estimates is limited, No statistically significant differences among biological agents were found with respect to harm. Conclusions: This study suggests there are differences in effectiveness but not in harm among biological agents applied as monotherapy in RA. Patient-important benefits such as ACR50 occurred more frequently with etanercept or tocilizumab monotherapy than with other biological agents. Further, in recommended dose, both etanercept and tocilizumab were superior to adalimumab and certolizumab pegol. Despite no differences between rituximab and etanercept or tocilizumab were found, our confidence in these findings were limited. In conclusion evidence suggests etanercept or tocilizumab to be the most appropriate choice for RA patients treated with biological monotherapy. References: PROSPERO: CRD42012002800 Acknowledgement: The Parker Institute is supported by grants from the Oak Foundation. Funding: This study, including the protocol, was supported by a grant from Roche, Denmark; the grant was provided as an unrestricted grant to Musculoskeletal Statistics Unit, The Parker Institute. The sponsor of the study had no role in data collection, data analysis, data interpretation, or writing of the abstract. The corresponding author had full access to all the data in the study and had the final responsibility for the decision to submit for publication. Disclosure of Interest: S. Tarp Grant/research support from: AbbVie, Roche, Speakers bureau: Pfizer, MSD, D. Furst Grant/research support from: Abbott, Amgen, BMS, Janssen, Pfizer, Roche/Genentech, UCB, Speakers bureau: Abbott and UCB (CME only), A. Døssing: None declared, M. Østergaard Grant/research support from: Abbvie, BMS, Boehringer-Ingelheim, Celgene, Eli-Lilly, Centocor, GSK, Janssen, Merck, Mundipharma, Novartis, Novo, Pfizer, Schering-Plough, Roche, Takeda, UCB, Wyeth, T. Lorenzen Consultant for: Pfizer and Roche, M. Hansen Consultant for: Roche, J. Singh Grant/research support from: Takeda, Savient, Consultant for: Savient, Takeda, Regeneron, Iroko, Merz, Bioiberica, Crealta, Allergan pharmaceuticals, E. Choy Grant/research support from: Abbott Laboratories, Allergan, Amgen, AstraZeneca, Biogen, BMS, Boehringer Ingelheim, Celgene, Chugai Pharma, Daiichi Sankyo, Eli Lilly, Ferring Pharmacuetical, GSK, Hospira, ISIS, Jazz Pharmaceuticals, Jenssen, MedImmune, Merrimack Pharmaceutical, MSD, Napp, Novimmune, Novartis, Pfizer, Regeneron, Roche, Sanofi-Aventis, Synovate, Tonix, and UCB., M. Boers Consultant for: Pfizer, BMS, Novartis, Takeda, M. Suarez-Almazor Grant/research support from: Pfizer, Consultant for: Abbvie, L. Kristensen: None declared, H. Bliddal Grant/research support from: Abbott, Bristol-Myers Squibb, Lilly, MSD, Pfizer, Roche, UCB, Wyeth, R. Christensen Grant/research support from: Abbvie, MSD, Mundipharma/Norpharma, Novartis, Roche, Consultant for: Abbvie, Bristol-Myers Squibb, Eli Lilly, Hospira, MSD, Novartis, Pfizer, Roche